Topoclimatic differentiation of the area of the Słowiński National Park, northern Poland - Kolendowicz, Leszek; Bednorz, Ewa (Quaestiones Geographicae, 2010)
The primary objective of the study was to elaborate a synthetic topoclimatic map of the area of the Słowiński National Park (SNP). The spatial scopes of individual types of topoclimate were distinguished using the method proposed by Paszyński (1999). Pursuant to this method, the topoclimatic classification – and subsequently topoclimatic charting – is performed on the basis of an analysis of the exchange of energy between the atmosphere and its base. The research conducted allowed us to determine that the SNP contains 12 types of local climate, and also to designate the spatial scopes thereof.